THE EFFECTIVENESS AND CHALLENGES OF PERSONAL BRANDING AND PROFESSIONAL DEVELOPMENT PLANNING - Sulistioyuwono, Ahmad Budi (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aimed primarily to identify the primary obstacles that individuals face in their career paths, to assess how Personal Development Planning (PDP) and personal branding can serve as purposeful responses to these obstacles, and to synthesize findings on how these strategies together enhance employability, career insight, and ongoing professional development. This study presents a structured synthesis of 27 scholarly works examining the effectiveness of personal branding and professional development planning (PDP) across diverse sectors, including higher education, journalism, public service, tourism, and digital media. Drawing on both empirical and conceptual research, the review identifies key interventions and strategic functions, classifying their outcomes as effective, ineffective, or contextually dependent. The findings suggest that effective personal branding hinges on authenticity, cultural alignment, and structured implementation, often resulting in enhanced employability, identity clarity, and strategic visibility. However, challenges persist, including branding fatigue, institutional rigidity, cultural misfit, and the lack of validated measurement tools. Studies also reveal psychological costs associated with overbranding and ethical concerns in identity management. This review underscores the importance of context-sensitive, measurable, and supportive branding frameworks, and calls for greater integration of narrative-building tools in formal education and career development systems